2008
DOI: 10.1074/jbc.m804296200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-29 Functions Cooperatively with Interferon to Induce Antiviral Gene Expression and Inhibit Hepatitis C Virus Replication

Abstract: The interferon (IFN)-related cytokine interleukin (IL)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 53 publications
(68 reference statements)
0
68
0
Order By: Relevance
“…IFNk/IL-29 shares with type I interferon the same Jak/Stat signalling pathway driving expression of a common set of genes although IFNk/IL-29 binds to a distinct membrane receptor [37]. However, similar to IFNb, IFNk failed to induce S100 gene expression ( Fig.…”
Section: Il-10 and Various Interferones Did Not Alter S100 Gene Exprementioning
confidence: 95%
“…IFNk/IL-29 shares with type I interferon the same Jak/Stat signalling pathway driving expression of a common set of genes although IFNk/IL-29 binds to a distinct membrane receptor [37]. However, similar to IFNb, IFNk failed to induce S100 gene expression ( Fig.…”
Section: Il-10 and Various Interferones Did Not Alter S100 Gene Exprementioning
confidence: 95%
“…Hepatitis C virus could be an important target of IFN-ks, as suggested by genetics studies showing that genetic variation in the gene encoding IFN-k3 predicts hepatitis C treatment-induced viral clearance [110][111][112][113]. Although mouse liver cells might not respond to IFN-ks, it has been shown that IFN-k1 in combination with either IFN-a or IFN-c is able to block hepatitis C virus replication in human hepatocytes, indicating that IFN-ks may be used for treatment of this disease [114].…”
Section: Il-24mentioning
confidence: 99%
“…Therefore, a treatment regimen of both IFN-a and IFN-l might be more promising than the current IFN-a therapy. Pagliaccetti et al reported a cooperative activity of IFN-l1 and IFN-a or IFN-g in inhibiting HCV replication and inducing antiviral gene expression [14]. A Phase Ib clinical trial of IL-29 (IFN-l1) has reported antiviral effects against HCV and low toxicity [15].…”
Section: Impact Of Il-28b Snps On Control Of Hepatitis C Virus Infectmentioning
confidence: 99%